Dengue Vaccine: Challenges and Limitations - Quazi Manjurul Haque,; Syed Minhaj Uddin Ahmed,; Md Arifur Rahman,; Abdullah Akhtar Ahmed,; Md Zulfikar Ali, (KYAMC Journal, 2024)
Dengue is a common mosquito-transmitted viral infectious disease. Due to global warming and other climate changes, the dengue virus vector Aedes aegypti mosquito is breeding rapidly and spreading the dengue worldwide. As a result, every year, millions of people are infected by the dengue virus and tolls thousands of lives across the world. World Health Organization (WHO) has given a terrible message that dengue can become as an epidemic. Therefore, the invention of an effective dengue vaccine is a way to build the body’s immunity to fight against the disease. Efforts to develop a vaccine against dengue have been ongoing for decades. Currently, Dengvaxia is approved for use by individuals to prevent dengue with some limitations. Another vaccine, Qdenga is also shown to be effective against verities of dengue virus serotypes but this vaccine is not approved by the USA Food and Drug Administration (FDA) yet. Neither Dengvaxia nor Qdenga has approved in Bangladesh and other low and middle-economic countries due to its conservative approach, controversy and lack of WHO guidelines on dengue vaccine. KYAMC Journal Volume: 14, No: 03, October 2023: 172-174.